Dynamics of the sentences system in Balinese-Malay language - Suparwa, I Nyoman; Satyawati, Made Sri (Penerbit Universiti Kebangsaan Malaysia, 2017)
Balinese-Malay language found today; called as base karang ni is a legacy of the previous Malay called base lame 'old Balinese-Malay'. It is spoken by the Malay community of West and East Loloan Village, Jembrana, Negara, Bali. Since 17th century this language has developed and has gone through various dynamics of retention and innovation. The problems of the research were about how the basic sentence system; dynamics of morphological and syntantic elements of productive prefixes and relatively labile sentences; and dynamics of phonological elements in Balinese-Malay language sentences were. Generative theories and explanatory descriptive method through the speech analyzer program were applied in the research. The results of this study showed that the use of some lexicons such as tanak ‘to cook’, can be attached by prefix me-, as in metanak in Balinese-Malay. The construction appears to be similar in bahasa Indonesia, aside from the /t/ which is apparently not dropped. In terms of its system, prefix me- is equal to prefix ber- in Indonesian, and prefix ŋ- is equal to me-. Historically, the difference between old Balinese-Malay with the modern ones can be seen from the softening of /h/ in the final position of seh. The duration of old Balinese-Malay was also found longer than the modern one and the East dialect was longer than the West. It was proved that the East Loloan is the area of the origin Balinese-Malay in Bali; meanwhile West Loloan is the development area.